Self-Affirmation Reduces Delay Discounting of the Financially Deprived - Moeini-Jazani, Mehrad; Albalooshi, Sumaya; Seljeseth, Ingvild Müller (Frontiers in Psychology, 2019)
Financial deprivation is associated with excessive discounting of delayed rewards. In the present research, we argue that this counterproductive tendency may be driven, at least in part, by the aversive and self-threatening nature of experiencing financial deprivation. Accordingly, we propose that self-affirmation—an intervention known to buffer negative consequences of psychological threats—may reduce delay discounting of the financially deprived. Results of two high-powered, preregistered experiments support this proposition. Specifically, in Study 1 (n = 546), we show that among participants with relatively lower incomes, self-affirmation effectively reduces delay discounting. In Study 2 (n = 432), we manipulate the feeling of financial deprivation and demonstrate that self-affirmation reduces delay discounting among those who feel financially deprived. We also examine the underlying process of our proposed effect and find that self-affirmation bolsters a sense of personal control among those who feel financially deprived, which in turn reduces their delay discounting (Study 2). Overall, our findings show that psychological interventions that buffer self-threats and foster a sense of personal control can be applied to reduce myopic tendencies of the financially deprived in decision-making.